2008
DOI: 10.1097/mcg.0b013e318030e3ab
|View full text |Cite
|
Sign up to set email alerts
|

Changing Epidemiology of HCV and HBV Infections in Northern Italy

Abstract: Our study provides a new picture of HCV and HBV epidemiology in Northern Italy, with these features: (1) a cohort effect showing a reduction of HCV infection in the elderly, possible due to age-related mortality; (2) an unchanged overall prevalence of HBV infection, despite continuing immigration of subjects from endemic countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
52
3
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 26 publications
8
52
3
1
Order By: Relevance
“…These differences can be related to the variability in the prevalence of anti-HCV antibodies in the general population of these two Mediterranean countries, being much higher in Italy. 22,23 Our study also fails to demonstrate that male gender is a risk factor for HCC in PBC when considering the overall series from Italy and Spain, thus totaling the highest series published. This is opposed to results reported in other studies, 4,5,14-16 a discrepancy that can be explained from the duration of follow-up and the number of patients evaluated.…”
Section: Discussioncontrasting
confidence: 73%
“…These differences can be related to the variability in the prevalence of anti-HCV antibodies in the general population of these two Mediterranean countries, being much higher in Italy. 22,23 Our study also fails to demonstrate that male gender is a risk factor for HCC in PBC when considering the overall series from Italy and Spain, thus totaling the highest series published. This is opposed to results reported in other studies, 4,5,14-16 a discrepancy that can be explained from the duration of follow-up and the number of patients evaluated.…”
Section: Discussioncontrasting
confidence: 73%
“…Additionally, this prevalence is also similar to the rate found in adolescents with immunization rates up to 98% in the state (1.4% and 0.6%) Tonial et al, 2011), the rate reported in Portugal for adolescents with a mean age of 14 years old (0.6%) (Antunes, Macedo, Estrada, 2004), and the rate reported in Italy for individuals up to 24 years old (1.0%) (Fabris et al, 2008); however, it is inferior to the rate reported by Nascimento et al (2008) in first-time eligible blood-donors from north, northeast and southeast Brazil (2.9%) and to the rate found in blood donors in south Brazil (15.6%) (Martelli et al, 1999) and the MRF (4.5%) (Rosini et al, 2003).…”
Section: Discussionsupporting
confidence: 60%
“…Tonial GC et al -HBV and vaccination in Itajaí, southern Brazil and also to ensuring an adequate allocation of financial resources 15 . Thus, the aim of this study was to determine the prevalence of HBV markers and assess hepatitis B vaccination coverage in voluntary adolescents, junior high (secondary school) students, in the City of Itajaí, State of Santa Catarina, Brazil.…”
Section: Discussionmentioning
confidence: 99%